Impact of the COVID-19 pandemic on trade and remittances in Eurasia - Romashkin, Roman (2020)
Roman Romashkin POLICY SEMINAR Virtual Event - Food Policy Research and Capacity Development in Eurasia Co-Organized by the Eurasian Center for Food Security (ECFS), World Bank Group, and IFPRI DEC 2, 2020 - 07:30 AM TO 09:00 AM EST